Green building index malaysia-qualitative survey on vernacular housing type in malaysia - Ahmad Syafri Bin Abdullah, Ahmad Syafri (2010)
The results from the project show that vernacular buildings scores much higher than the modern terrace house. This shows that vernacular residential buildings are much more environmental friendly than modern terrace house.